The Difference Between the Conventional Warm Compress and Tepid Sponge Technique Warm Compress in the Body Temperature Changes of Pediatric Patients with Typhoid Fever - Aaulya Kartini Dg Karra; Muh Aswar Anas; Muhammad Anwar Hafid; Rosdianah Rahim (Universitas Airlangga, 2019)
Introduction: The use of warm compresses and warm sponge techniques as a modality therapy for the management of fever in typhoid children has a good influence. The purpose of this research was to learn of the differences between conventional warm compress and the tepid sponge technique as related to the body temperature changes of pediatric patients with typhoid fever. A fever that does not get a good standard of treatment can cause dehydration, neurological damage and febrile seizures.Methods: The research design was quasi-experiment with two groups pre-post test. The population was taken from the Kampili Community Health Center while the 20 samples were taken using the purposive sampling technique. Conventional warm compresses were placed on the forehead, while warm tepid sponges were compressed and placed on the forehead, armpits and the folds of the thighs simultaneously.Results: . The data of the results were significance tested using the General linear model repeated measure (p value 0.03 for conventional warm compresses and p value 0.01 on a warm compress tepid sponge technique).Conclusion: Statistically, the warm compress tepid sponge technique is more meaningful and qualitatively, the temperature change is better after the compression.